AC resistance of planar power inductors and the quasidistributed gap technique. - Jiankun Hu
Low-AC-resistance planar or foil-wound inductors constructed using a quasidistributed gap comprising multiple small gaps that approximate a distributed gap are analyzed. Finite-element simulations are used systematically to develop a model broadly applicable to the design of such quasidistributed gap inductors. It is shown that a good approximation of a distributed gap is realized if the ratio of gap pitch to spacing between gap and conductor is less than four, or if the gap pitch is comparable to a skin depth or smaller. Large gaps can reduce AC resistance, but for most practical designs gap length has little effect. A closed-form expression, which closely approximates the AC resistance factor for a wide range of designs, is developed. The methods are illustrated with an inductor for a high-ripple-current fast-response voltage regulator module (VRM) for microprocessor power delivery
Keywords: AC resistance; Closed-form expression; Eddy currents; Finite-element simulations; Foil-wound inductors; Fringing effects; Gap length; Gap pitch; High-ripple-current fast-response voltage regulator module; Low-AC-resistance planar inductors; Magnetic devices; Microprocessor power delivery; Multiple small gaps; Planar power inductors; Power conversion; Proximity effect; Quasidistributed gap technique; Skin depth; Voltage regulator modules